STYLISTIC ANALYSIS OF CLASSICAL AND MODERN LITERARY WORKS IN A LITERARY WORK - Irenne Edelwis Rondonuwu; Chika Laras Pramestuti; Putri Angel Lestari; Ichsan Fauzi Rachman (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
This research examines the differences in language style in two Indonesian literary novels, namely "Ronggeng Dukuh Paruk" by Ahmad Tohari (representative of classical literature) and "Laskar Pelangi" by Andrea Hirata (representative of modern literature). This research uses a qualitative descriptive method, focusing analysis on language styles, such as similes, personification, hyperbole and metaphor. In the classic literature "Ronggeng Dukuh Paruk", one finds the use of personification and metaphor to describe situations and characters. For example, coconut leaves depict suppressed anger. On the other hand, in the modern literature "Laskar Pelangi", the language style tends more towards allegory, such as juxtaposing teachers with the roles of mentor, guardian, friend, teacher and spiritual teacher. This research provides an in-depth understanding of the evolution of language styles in Indonesian literature, considering differences in era and societal context. In conclusion, stylistic analysis can reveal characteristic differences between classical and modern literature, providing broader insight into the development of Indonesian literature.